Pengaruh Electronic Word of Mouth dan Komunikasi Pemasaran Digital terhadap Niat Berasuransi (Studi Kasus pada Pengikut Akun Instagram PT Equity Life Indonesia) - Yuliarti Yuliarti; Cahyanti Baskoro Ratri (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the influence of electronic word of mouth (e-WOM) and digital marketing communications on insurance purchase intentions, using a case study of followers of PT Equity Life Indonesia's Instagram account. The research was conducted using a survey method and purposive sampling technique, with 100 respondents who were followers of PT Equity Life Indonesia's Instagram account. The collected data were analyzed using multiple linear regression to test the relationships between the variables. The results of the study confirm that both e-WOM and digital marketing communications have a significant impact on insurance purchase intentions. These findings suggest that effective management of e-WOM and the application of appropriate digital marketing strategies can encourage insurance purchase intentions among PT Equity Life Indonesia's Instagram followers. Consequently, PT Equity Life Indonesia has been successful in consistently stimulating its followers through social media, leading to an increased intention to purchase insurance. This study provides valuable insights for insurance marketers in designing more effective strategies in the digital era.